Quotidian use of new media and sociocultural change in contemporary Kenya. (1st June 2019) - Nielsen, Poul Erik
This article examines how ordinary people in rural and urban areas in Kenya ascribe meaning to their daily use of information and communication technologies (ICTs) including media in ever changing communication ecologies and how the use of new ICT interrelates with processes of sociocultural change in everyday life. Taking as point of departure a semi-ethnographic social constructivist approach based on observations and semi-structured life world interviews the study presents an exploratory analytical bricolage around themes like power, knowledge and gender. The findings identify a simultaneous and seamless integration of the different new media that lead to significant open-ended processes of sociocultural change characterized by complexities, ambiguities, continuities, ruptures and inertia rather than dramatic irreversible changes. These findings call for a new paradigm in media studies focusing on communication ecologies and everyday uses of ICT where continuity and inertia are more seriously taken into accounts in processes of sociocultural change.